Influence of cardiovascular condition on retinal and retinal nerve fiber layer measurements - Garcia-Martin, Elena (PLoS One, 2017)
OBJECTIVE: To assess changes in the retinal nerve fiber layer (RNFL) and macula in subjects with cardiovascular risk factors or subclinical ischemia. DESIGN: Prospective and observational study. METHODS: A total of 152 healthy men underwent cardiovascular examination, including quantification of subclinical atheroma plaques by artery ultrasound scans, blood analysis, and a complete ophthalmic evaluation, including spectral-domain optical coherence tomography. The variables registered in cardiovascular examination were quantification of classic major risk factors, subclinical atheroma plaques by artery ultrasound scans, and analytical records. The ophthalmic evaluation registered RNFL and macular thickness. RESULTS: Mean subject age was 51.27±3.71 years. The 40 subjects without classic cardiovascular risk factors did not show differences in RNFL and macular thicknesses compared with the 112 subjects with at least one risk factor (except in sector 9 that showed higher thicknesses in subjects with ≥1 risk factor). Comparison between the group of subjects with and without atheroma plaques revealed no differences in RNFL and macular thicknesses. The sub-analysis of subjects with subclinical atheroma plaques in the common carotid artery revealed a significant reduction in central macular thickness in the left eye compared with the right eye (p = 0.016), RNFL in the superior quadrant (p = 0.007), and the 11 o’clock sector (p = 0.020). Comparison between smokers and nonsmokers revealed that smokers had significant thinning of the central macular thickness (p = 0.034), the nasal RNFL quadrant (p = 0.006), and the 3 and 5 o’clock sectors (p = 0.016 and 0.009). CONCLUSIONS: Classic cardiovascular risk factors do not cause RNFL or macular thickness reduction, but tobacco smoking habit reduces nasal RNFL thickness. Subclinical atherosclerosis in the common carotid artery associates a reduction in central macular and nasal RNFL quadrant thicknesses in the left eye compared with the right eye.